LIPOPHILIC AND STRUCTURE ACTIVITY RELATIONSHIPS STUDY OF THIOSEMICARBAZONES AND DERIVATIVES - GBAGUIDI, A. (My University, 2021)
Traditionally, small molecules have been a reliable source for discovering novel biologically active compounds because these molecules are easily synthesized and their smooth structural optimization would usually lead to a feasible candidate compound. Here, some thiosemicarbazones, N(4)-methyl and N(4)-phenyl-3-thiosemicarbazones were synthesized in good yield (52-84%), characterized and then their anti-parasitic activity were evaluated. The structure and lipophilic-activity relationships of compounds were particularly studied. Among them, some products exhibited trypanocidal activity with their half inhibitory concentration (IC50 ? 10 micromolar ??M?) especially compounds L1-3, D2, B3, C3, D1 (from 2 to 8.73 ?M). Other showed moderate antitrypanosomal activity with their IC50 between 12 to 87 ?M (L4, C2, C1, B2) while certain showed little activity (IC50 ? 100?M). Some active products turned out quick selective on the parasite with their selectivity index greater than to unit (SI ? 1). Several factors including lipophilicity, steric and electronic effects of the substituents have played a vital role in this activity. The elongation of the carbon chain of the carbonyl, the substitution on a phenyl radical, the fixing of a methyl or phenyl on the N(4) nitrogen atom induced significantly the increased trypanocidal activity of compounds. This is the case specifically of N(4)-methyl and especially of N(4)-phenyl-substituted thiosemicarbazones. Such compounds could be able to have applications in the treatment of parasitic diseases
Keywords: Synthesize thiosemicarbazones trypanocidal lipophilicity selectivity